Resiliência e velhice: um estudo de fatores de risco e de proteção na saúde do idoso - Ferreira, Camomila Lira (2010)
Resilience consists of a capacity to adapt and overcome situations of risk, from the aid of protective factors. This construct constitutes a process of preventive and multidimensional present in all stages of human development. During this development, it has been immersed in the elderly biopsychosocial changes resulting from the aging process. In this sense, there was a need for a multidisciplinary study, combining psychology, medicine, nursing, social work and gerontology in order to check the resilience, its risk factors, such as life events and health, and protection, such as self-esteem and social support. For this, we performed a descriptive exploratory study of cross-sectional nature, along with a convenience sample consisting of 65 elderly users of the public health of the district east of the city of Natal/RN, Brazil. This research allowed the collection of socio-demographic, economic, relational, physical, biological and psychological in understanding the aging process. It is observed that the studied sample socio-economic status and chronic health conditions in their own lives and their families, that demand for care and attention every day, are resilient, have faced significant losses, have positive self-esteem and social support perceived as external satisfactory. Given this multidimensional nature, the aging process deserves the attention of many professionals and health policies, seeking provide to the elderly a better living conditions and mechanisms that promote well-being and health